Evolution of desmosomal genes in teleost fish and expression analysis of desmosomal cadherins in the gilthead sea bream (Sparus aurata) - Silva, Melina Coelho da (2017)
Dissertação de mestrado, Biotecnologia, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2017